Stress Induced Cardiomyopathy with Midventricular Ballooning: A Rare Variant - Muhammad Umer Siddiqui; Michael C. Desiderio; Nicholas Ricculli; Arthur Rusovici (Case Reports in Medicine)
Stress cardiomyopathy (SCM) also referred to as the “broken heart syndrome” is a condition in which intense emotional or physical stress can cause fulminant and reversible cardiac muscle weakness. SCM most commonly involves the apical segment of left ventricle but newer and rare variants have recently been seen reported. We here report a case of rare midventricular variant of stress related cardiomyopathy. A 72-year-old female with past medical history, only significant for SVT, presented with an episode of severe substernal chest pain while hiking with her husband. She felt a significant heaviness in her chest and was short of breath. During her hospitalization she was found to have positive cardiac enzymes. EKG showed 1 mm downsloping ST segment changes. Ventriculogram during left heart catheterization revealed dyskinetic midventricle. Patient was diagnosed with midventricular SCM. The patient was placed on ACE inhibitor and beta-blocker and discharged in a well-compensated state. We suggest identifying these patients by standard lab testing, electrocardiography, echocardiography, and left heart coronary angiography and ventriculography. Management of this unique entity is similar to the other variants with close observation and treatment of accompanying heart failure, valvular dysfunction, and any arrhythmias that may develop.